Recycling of residual soil nitrogen in a lowland rice-sweet pepper cropping system - Shrestha, R.K.; Ladha, J.K. (Wiley, 2000)
Residual mineral N after the dry season (DS) crop in an intensive rainfed lowland is lost upon flooding for rice (Oryza sativa L.) planting. The conservation and recycling of this N are essential for maintaining groundwater quality and system sustainability. Experiments conducted in rice–sweet pepper (Capsicum annuum L.) cropping systems in farmers' fields aimed (i) to quantify the levels of soil mineral N after the incorporation of residues of different dry‐to‐wet (DTW) transition crops in combination with two formulations of fertilizer N, as well as their effects on rice yields and N use efficiencies, and (ii) to estimate the soil N balance. Significant amounts of NH4–N accumulated in soil at 15 d after incorporation of residues of indigo (Indigofera tinctoria L.) alone (12 kg ha−1) and indigo mixed with mungbean (Vigna radiata L.) residue (24 kg ha−1), and at 60 d after incorporation of maize (Zea mays L.) residue (8 kg ha−1). Soil NH4–N in treatments with maize residue was lower than that from indigo and mungbean, but it was improved when maize residue was mixed with fertilizer N. Nitrate N peaked in the upper soil layer before flooding occurred, followed by its leaching and disappearance later. Crop residues incorporated in the plot maintained low NO3 throughout the soil profile. The crops during DTW transition reduced N losses by 33 to 72%, and residue incorporation supplied N equivalent to 87 kg ha−1 to rice. The results suggest that a transition crop alone cannot completely reduce the N losses; therefore, strategies for reducing N fertilizer rates to better match N demand of the DS crop are needed.